A few steps forward and no steps back: long‐distance dispersal patterns in small carpenter bees suggest major barriers to back‐dispersal. (11th November 2014) - Rehan, Sandra; Schwarz, Michael
Abstract: Aim: Inequality between rates of forward and backward dispersal is one mechanism that will produce regional differences in biotic composition. Any such differences will affect ecosystem assembly. Thus, it is important to understand why unequal dispersal rates might occur. Recent studies have indicated strong differences between forward and backward dispersal in two major bee groups, Hylaeinae and Allodapini. Here, we use a third bee group, tribe Ceratinini, to determine whether this might be a more general phenomenon. Location: Worldwide. Methods: Ceratinini is globally distributed (excepting Antarctica) and contains the single genus Ceratina and 21 subgenera, most of which are endemic to continents. We examined the phylogeny of Ceratinini using sequence data from three genes and 99 species, and inferred ancestral distributions using Bayesian and maximum likelihood approaches. Results: We show that the tribe Ceratinini had an African origin in the early Eocene. This was followed by four dispersals out of Africa in the Eocene and early Oligocene and three further dispersals between the Miocene and the present. There has been no back‐dispersal of Ceratinini to Africa. The lack of back‐dispersal cannot be explained by species abundance in non‐African regions, and physical barriers to back‐dispersal seem unlikely. Main conclusions: Our results are similar to findings for two other major bee groups and indicate that back‐dispersal is very rare. It is unlikely that physical barriers can explain these patterns. However, dispersal patterns might be explained by assembly rules such as niche pre‐emption or by reduced opportunities for escaping into enemy‐free space. At a continental level, it is likely that the composition of bee fauna is more strongly influenced by very early dispersal events rather than by later physical barriers to dispersal.